BULLYING – PROBLEMS OF RECOGNITION AND FIGHTING THE PHENOMENON - Teacă, Mihaela Ioana (International Journal of Legal and Social Order, 2024)
Bullying is aggressive, repeated and intentional behavior that occurs within unequal power relations and can have serious consequences for children's health and well-being. It is important that every child is protected against bullying and has adequate support and resources to deal with it. Child protection against bullying involves an integrated action by families, schools, communities and authorities to prevent, identify and manage bullying situations. It is essential to promote a climate of respect, empathy and tolerance among children and young people, as well as to encourage open and non-violent communication for conflict resolution. Schools have a crucial role in the prevention of bullying, by implementing educational policies and programs that develop students' social and emotional skills, encourage positive relationships between them, and provide support and prompt intervention in the event of bullying incidents. Teachers and school staff have a responsibility to be aware of the signs of bullying and to intervene appropriately to protect the children involved.